Numerical study of transient aerodynamic forces acting on a ski jumper considering dynamic posture change from takeoff to landing - Yamamoto, K.; Nishino, T.; Bale, R.; Shimada, T.; Miyamoto, N.; Tsubokura, M. (Sports Biomechanics, 2022)
This study was designed to develop a computational fluid dynamics (CFD) method for unsteady analysis of a series of ski jump movements with attitude changes, and to analyse the aerodynamic characteristics of an expert jumper over the entire ski jump movement. Two ski jumpers participated in this study. A sensor-based motion capture suit was used to capture the jumper`s posture during the actual ski jump. A three-dimensional computer graphics animation was created by superimposing the joint angles obtained from the motion measurements of the 3D shape of the athlete. The unsteady aerodynamic forces acting on the ski jumper, from the takeoff to the landing, were then calculated using CFD. A time-varying spatially uniform flow was specified as the inflow boundary condition of the computational domain. The results indicated that both the lift and drag forces of the expert jumper increase rapidly during the initial flight when the jumper`s posture changes drastically. Thereafter, drag force decreased considerably, but the decrease in the lift force was less drastic. Later in the flight phase, the lift force acting on the expert jumper increased, and throughout the flight phase, the lift-drag ratio of the expert jumper remained higher than that of the unskilled jumper.